Factors Affecting Biometrics Using for Crime Control: Case Studies from Police Stations in Thailand - Ieamim, Somsak; Sirisunhirun, Somboon (Journal of Ecohumanism, 2025)
This study aimed to examine the situation and analyze problems in law enforcement using biometrics for crime control and to study the success factors affecting efficiency and effectiveness in policymaking. The concepts and models of Van Meter and Van Horn (1975), Paul Sabatier and Danial Mazmanian (1980), Lipsky (1980), Berman and Mclaughlin (1977), Collaborative Governance, efficiency and effectiveness were employed in this study. This was qualitative research using in-depth interviews and a focus group discussion. The key informants included police officers, the public, and scientists. For the qualitative analysis, content analysis, typology, and taxonomy analysis were employed. The research findings revealed that the problems in law enforcement using biometrics for crime control included the lack of supporting laws for officers’ authorities to collect biometric databases, explicit responsibilities, personnel, budget, equipment, and integration and exchange of data between agencies. Therefore, for a successful policy, the Royal Thai Police must prioritize management, big data, innovation, and public satisfaction with the policy. The development aims to create innovations in law enforcement to enhance efficiency and effectiveness in public administration.